The influence of fatigue in evertor muscles during lateral ankle sprain - Rodrigues, Karina A. [UNESP]; Soares, Renato J.; Tomazini, José E. [UNESP] (Elsevier, 2019)
Ankle sprain in plantarflexion and inversion is one of the most common injuries occurring in daily activities and sports. Although acute symptoms may resolve quickly, many individuals have reported persistent pain and instability. Thus, understanding the factors that contribute to the occurrence of this type of injury is extremely important. Although sprains are multifactorial, a relationship can be established between sprain and fatigue. Therefore, the present study examined the latency and intensity of activation of the peroneus longus and brevis muscles under conditions of fatigue. Twenty-three women participated in the study, including 12 with functional instability of the ankle and 11 without a history of sprain. To induce fatigue, the volunteers maintained the force of eversion and plantarflexion at 70% of the maximum voluntary isometric contraction for as long as possible until a 10% decline in the rated force occurred. Ten simulations of ankle sprains were performed before and after fatigue at random for each side, with simultaneous recordings of the electromyographic signals, using a simulator platform for inversion sprain and plantarflexion. As a result, after fatigue, no change in latency was observed. However, a reduction in the intensity of contraction of the muscles analyzed in both groups was observed. Neuromuscular control was concluded to be compromised in situations of fatigue, while differences in muscle behavior were not observed between stable and unstable ankles.
Keywords: Ankle sprain; Chronic ankle instability; Electromyography; Muscular fatigue